2003
DOI: 10.1021/ol0341703
|View full text |Cite
|
Sign up to set email alerts
|

New Fe(III)-Mediated Radical Cascade Reactions of Cyclopropyl Silyl Ethers

Abstract: [reaction: see text] Fe(III)-mediated ring opening of cyclopropyl ethers bearing a phenyl-substituted butenyl side chain leads to the generation of beta-keto radicals that undergo 5-exo cyclization followed by a novel cascade sequence resulting in the formation of tricyclic ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In 1984, Okamoto reported the hydration of styrenes using cobalt or iron complexes and NaBH 4 under air (Scheme , eq 1). Quite recently, Beller and co-workers reported the synthesis of oximes from styrenes using a catalytic amount of iron phtalocyanine [Fe(Pc)] in the presence of NaBH 4 , and Boger and co-workers reported the hydration of trisubstitute olefins of vinblastine and β-citronellol using excess iron salts and NaBH 4 under air . A radical mechanism has been proposed for these reactions. ,, Nevertheless, an application of these methods using iron compounds and NaBH 4 to radical cyclizations has never been explored . Herein, we report iron-catalyzed redox radical cyclizations of 1,6-dienes using NaBH 4 (Scheme , eq 2) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1984, Okamoto reported the hydration of styrenes using cobalt or iron complexes and NaBH 4 under air (Scheme , eq 1). Quite recently, Beller and co-workers reported the synthesis of oximes from styrenes using a catalytic amount of iron phtalocyanine [Fe(Pc)] in the presence of NaBH 4 , and Boger and co-workers reported the hydration of trisubstitute olefins of vinblastine and β-citronellol using excess iron salts and NaBH 4 under air . A radical mechanism has been proposed for these reactions. ,, Nevertheless, an application of these methods using iron compounds and NaBH 4 to radical cyclizations has never been explored . Herein, we report iron-catalyzed redox radical cyclizations of 1,6-dienes using NaBH 4 (Scheme , eq 2) …”
mentioning
confidence: 99%
“…Fe−C bond cleavage of complex 8 by O 2 followed by cyclization of the resultant radical intermediate 9 gives the new radical 10 . When FeCl 3 is employed as an iron source, the addition of a chlorine atom to the radical 10 gives chlorinated product 2a . On the other hand, in the case of using a catalytic Fe(Pc), the radical 10 was trapped by O 2 to give peroxide radical 11 .…”
mentioning
confidence: 99%
“…Herein, we report an efficient radical nitro-cyclization of 1,6-dienes using Fe(NO 3 ) 3 ·9H 2 O to give cyclic nitro compounds. To the best our knowledge, the radical cyclization of 1,6-dienes initiated by introducing a nitro group has never been reported. …”
mentioning
confidence: 99%
“…For example, they found that treatment of silyl-protected cylopropanols bearing a tethered alkene with iron(III) nitrate in the presence of various radical trapping reagents provided cyclic or polycyclic systems with functionalized carbon atoms in remote locations relative to the cyclopropanol-derived ketone (Scheme 57, a). 58 Interestingly, iron(III) nitrate mediated radical cyclizations conducted without a radical trap can give interesting products arising from a subsequent single-electron cyclization (Scheme 57, b). For instance, the initial radical generated from oxidation of cyclopropanol can participate in sequential 5-exo-trig cyclizations to give an oxy-radical.…”
Section: Scheme 56 Iron(iii) Chloride Mediated Synthesis Of Meta-subsmentioning
confidence: 99%